2022
DOI: 10.1155/2022/7073647
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Type 2 Diabetes and Fat Fraction in Liver and Pancreas: A Study using MR Dixon Technique

Abstract: Objective. The increased obesity results in ectopic fat deposits in liver and pancreas, which will affect insulin resistance and elevated plasma glucose with type 2 diabetes. To assess the relationship between obesity and ectopic fat deposits and diabetes, this study used the MR Dixon method for the quantification of liver and pancreas fat fraction (FF) in type 2 diabetes mellitus (T2DM) patients and healthy controls. Methods. The FF of whole liver (FFWL) and pancreas (FFWP), the maximum diameters of the pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In the present study, we observed that the SAT area is not associated with T2DM, which is consistent with previous findings ( 9 ). Additionally, we observed that SAT FF in T2DM patients was lower than in non-T2DM patients.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the present study, we observed that the SAT area is not associated with T2DM, which is consistent with previous findings ( 9 ). Additionally, we observed that SAT FF in T2DM patients was lower than in non-T2DM patients.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings were consistent with these results. However, it was found that HFF was not the independent risk factor for T2DM, which is consistent with the findings of Zheng et al ( 9 ). We speculate that hepatic fat deposition may not be an independent mechanism in the pathogenesis of T2DM, and its role may be influenced by VAT, which collectively play important modulatory roles in T2DM development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations